1976
DOI: 10.1002/hlca.19760590721
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und absolute Konfiguration von Clemastin und seiner Isomeren

Abstract: Synthesis and Absolute Configuration of Clemastine and its Isomers. -Sztmmary. Condensation of 4-chloro-cc-mothylbenzhydrylalkohol (1) with 2-(2-chlorocthyl)-l-methylpyrrolidinc (2) gavc an isomeric mixture of 2-[2-(p-chloro-cr-methyl-cc-phenylbenz)-loxy)ethyl]-l-methylpyrrolidine (3) and 4-(p-chloro-cr-phenylbenzyloxy)-l-methyl-hexahydroazepi1~ (4). The separation of the four possible optically active isomers of 3 is described and their absolute configuration established by degradation to (R)-and (S)-l-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…A recent report indicates that long term incubation of lymphocytes with cimetidine at 10~3 M or higher concentrations induces significant lymphocyte toxicity [30]. As regards the histamine H|-receptor antagonist clemastin, our data clearly suggest that the earlier re ported NKCC suppression induced by this com pound [15] is not explained by its antagonism of H|-receptors since a clemastin isomer with very low affinity for the pharmacological receptor [23] was equally effective in NKCC suppression. An alterna tive explanation for the suppressive effects of clemas tin would be its membrane-stabilizing properties, since this effect of clemastin is unrelated to receptor specificity [21].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A recent report indicates that long term incubation of lymphocytes with cimetidine at 10~3 M or higher concentrations induces significant lymphocyte toxicity [30]. As regards the histamine H|-receptor antagonist clemastin, our data clearly suggest that the earlier re ported NKCC suppression induced by this com pound [15] is not explained by its antagonism of H|-receptors since a clemastin isomer with very low affinity for the pharmacological receptor [23] was equally effective in NKCC suppression. An alterna tive explanation for the suppressive effects of clemas tin would be its membrane-stabilizing properties, since this effect of clemastin is unrelated to receptor specificity [21].…”
Section: Discussionsupporting
confidence: 53%
“…This suppression was seen to a similar extent when an isomer of clemastin (3-C) with very low H|-receptor affinity [23] was tested ( fig. 5).…”
Section: Effect O F Clemastin and Clemastin Isomers On Nkccmentioning
confidence: 66%
“…Later,t he Glorius group furtherd eveloped ad irected intramolecular sp 3 CÀHa rylation of 8-benzylquinoline for the enantioselective synthesis of triarylmethanes (Scheme 30). Using the rhodiumc atalyst allowed high yield of the products.…”
Section: Metal Catalyzed Càhfunctionalizationmentioning
confidence: 99%
“…[1] This class of molecules has also found ap rofoundr ole in the development of variouspharmaceutical agentswith interesting physiologically important properties which include antidepressive, antilaxative, antiarrhymthmic, diuretic,l ocal-anesthetic and anticholinergic activities. [2] For example, Clemastinew as developed as af irst generation Histamine H 1 antagonist for the treatment of allergicd iseases, [3] and wasl ater modified and developed into Cetrizineh ydrochloride, which acts as a second generation antagonist with more selectivityt owards H 1 receptors. [4] Interestingly,t he (S)i somer of Cetrizine hydrochloride is more potent than the corresponding (R)-isomer.…”
Section: Introductionmentioning
confidence: 99%
“…This extended study included the compounds of which the crystal structures are reported here: seven of the older types of H~ antagonist: methapyrilene (13) (Clark & Palenik, 1972), Z isomer of triprolidine (Pepinsky, Rathlev & Turley, 1959) and triprolidine (14) (James & Williams, 1974a) and (15), (R)-and (S)-chloropheniramine (16) and (17) (James & Williams, 1974b), diphenylpyraline (18) (Precigoux, Barrans, Busetta & Marsau, 1975), clemastine (19) (Ebnother & Weber, 1976), and cyproheptadine (20) (Birknes, 1977); five thiadiazole-l-oxide derivatives compounds, (21)-(25), that had been synthesized and screened for H~ antagonist activity; the isocytosines (26), (27) and (28). This extended study included the compounds of which the crystal structures are reported here: seven of the older types of H~ antagonist: methapyrilene (13) (Clark & Palenik, 1972), Z isomer of triprolidine (Pepinsky, Rathlev & Turley, 1959) and triprolidine (14) (James & Williams, 1974a) and (15), (R)-and (S)-chloropheniramine (16) and (17) (James & Williams, 1974b), diphenylpyraline (18) (Precigoux, Barrans, Busetta & Marsau, 1975), clemastine (19) (Ebnother & Weber, 1976), and cyproheptadine (20) (Birknes, 1977); five thiadiazole-l-oxide derivatives compounds, (21)-(25), that had been synthesized and screened for H~ antagonist activity; the isocytosines (26), (27) and (28).…”
Section: Molecular-modelling Studies On H~ Histamine Antagonistsmentioning
confidence: 99%